Report of Two Cases of Pelvic Inflammatory Disease Complicating Transcervical Frozen Embryo Transfer - Marta Benito Vielba; Javier Navarro Sierra; Claudia Giménez Molina; Marta Narváez Salazar; Ricardo Navarro Martín; María Pilar Conte Martín (Clinical and Experimental Obstetrics & Gynecology)
Background: Pelvic inflammatory disease (PID) complicating transcervical embryo transfer, not related to previous oocyte aspiration, is an extremely rare event. However, it can lead to severe complications. Case: We report two cases of pelvic infection related to transcervical frozen embryo transfer. The case of one patient was complicated by a pelvic abscess, which required percutaneous drainage, and the case of the other patient was complicated by ascites, which was positive for chlamydia. Conclusions: Despite there not being enough evidence to recommend cervical cultures or antibiotic prophylaxis in all cases of embryo transfer, it would be advisable in those cases with a personal history of PID.